Homeobox B2 is a potential prognostic biomarker of glioblastoma - Li,Ming (2020)
SUMMARY OBJECTIVES HOXB2 is a new prognostic indicator for lung cancer. But it is unclear whether HOXB2 holds an effect in glioblastoma (GBM) progression. The purpose of this article was to probe the influences of HOXB2 on GBM pathogenesis. METHODS HOXB2 expression level and prognostic power in GBM patients were analyzed. Then the mRNA and protein expression levels of HOXB2 in GBM cell lines were tested by qRT-PCR and western blotting. Cell proliferation, invasion, and migration were determined by CCK8 and transwell assay, severally. The protein levels of PI3K/AKT-pathway associated proteins were analyzed by western blotting. RESULTS The results indicated that HOXB2 was distinctly overexpressed in GBM patients and high expression of HOXB2 was related to a poor prognosis. Moreover, the expression of HOXB2 was higher in all GBM cell lines U251, U-87MG, GOS-3 than that in HEB cells (normal control). Meanwhile, decreased expression of p-PI3K and p-AKT were identified after HOXB2 knockdown. CONCLUSIONS These data demonstrated that HOXB2 had a vital role in GBM progression and could serve as a promising target for GBM treatment.